Chiral terahertz wave emission from the Weyl semimetal TaAs - Y. Gao (Nature Portfolio, 2020)
Here, the authors report photon-energy-dependent terahertz emission and ultrafast photocurrents from the Weyl semimetal, TaAs. The polarization control of the emission is achieved by excitation of the photocurrents whose direction and magnitude depend on the polarization of the femtosecond optical pulses.